Investigating the Underlying Mechanisms of Circular RNAs and Their Application in Clinical Research of Cervical Cancer - Liu, Jian; Zhu, He; Fu, Li; Xu, Tianmin (Frontiers in Genetics, 2021)
Circular RNAs（circRNAs）are a non-coding RNA molecules, and there are differential expressions in various diseases including cancer, suggesting that circRNAs can regulate certain diseases. CircRNAs act as miRNAs sponges, RNA binding proteins (RBPs) sponges, translation regulators and become an important part in regulating gene expression. Furthermore, because of its biomedical features in body fluids, such as high abundance, conservation and stability, circRNAs are seen as potential biomarkers for various cancers. Cervical Cancer （CC） as one of the main causes of cancer death in women, there have been a large number of studies to circRNAs as a new object to be evaluated in CC. Therefore, this review, by understanding the role of circRNAs in CC, may create innovative strategies in the future clinical diagnosis, treatment and prognosis of CC and promote the development of personalized and highly accurate cancer therapy.